The Life Cycle of Employee Engagement Theory in HRD Research. Issue 3 (August 2019) - Kwon, Kibum; Park, Jiwon
The Problem: Although the current proliferation of employee engagement research in human resource development (HRD) has advanced our theoretical understanding of the nature of employee engagement and its importance, the scarcity of practical knowledge has circumscribed our understanding of how to assess, boost, and sustain employee engagement in workplaces. The Solution: Examining the life cycle of employee engagement theory, we determined that employee engagement is in the initial stages of becoming a formal theory. A better understanding of the application of employee engagement theory would facilitate the development of more effective interventions for building employee engagement and would, in turn, strengthen the etiology of employee engagement, which represents a complex interplay of multiple variables involving individual and environmental factors. Key Stakeholders: This study contributes to the HRD literature by elucidating the need for greater attention to the practical applications of employee engagement theory in HRD scholars and scholar-practitioners' future research and practice.